Development of European bison population “Ozery” from Grodno region (European Bison Conservation Newsletter, 2015)
In 1998–2014, numbers of European bison „Ozery” population increased from 18 to 196 individuals. In this period 213 calves were born, the average coefficient of fecundity was 37.5%, and coefficient of births – 16.4%. Eight individuals died of natural causes. Average coefficient of mortality was 0.4%. The present home range of this population is 15–20 thousand ha during summer, and 6–8 thousand ha during winter. E. bison of this population are feeding as well in the forest as and agricultural fields and cultivated meadows.
Keywords: European bison; population dynamics; Belarus